Capturing the impacts of balancing caring and employment: a photovoice study of Filipino-Canadian transnational working carers. (1st May 2021) - Ilagan, Chloe; Williams, Allison; Sethi, Bharati; Maynard, Kevin
Abstract : An ageing population has resulted in an increase in informal care. Many carers balance employment with care, called 'working carers'. Research is lacking on minority ethnic working carers. This article explores the experiences of Filipino-Canadian working carers and the health impacts of their roles through qualitative photovoice methods. Participants took photographs recording their experiences. Data were collected from eight participants in Ontario from May to November 2017. Photographs and interviews revealed themes of: (1) transplanted values dictating attitudes to care; (2) challenges to personal health; and (3) coping mechanisms and sources of help. These findings address knowledge gaps as regards the experiences of Filipino-Canadian working carers.